Perilaku Masyarakat Terhadap Kegiatan Arisan Simpan Pinjam Dalam Perspektif Islam - Awali, Husni; Yamsiana, Erika (Departement of Sharia Economics, Faculty of Islamic Economics and Business, IAIN Pekalongan, 2021)
The purpose of this study is to determine the motivation of the community in their involvement in the savings and loan â€œarisanâ€ and how this is in the view of Islamic Economics. In this study, researchers used a qualitative method with a descriptive approach. Sources of research information come from primary and secondary sources of information. The results of the study stated that the motivation of the people who participated in the savings and loan â€œarisanâ€ activity was as one of the storage containers and to get their money back in an easy way. In the view of Islamic economics, this gathering is permissible and not unlawful. Arisan can be said to be haram if there are aspects of tyranny, gharar (uncertainty/speculation), and usury, so that this kind of gathering is haram.